Electric charge rotating around a black hole - Castiñeiras, Jorge; Crispino, Luís C. B.; Murta, Rodrigo; Matsas, George Emanuel Avraam [UNESP] (Sociedade Brasileira de Física, 2005)
We consider an electric charge rotating around a Schwarzschild black hole. We compute, using quantum field theory in curved spacetime at the tree level, the power emitted by the rotating charge minimally coupled to the Maxwell field. We also compute how much of the radiation emitted by the swirling charge is absorbed by the black hole.